Efeito da sazonalidade sobre as populações de três espécies de pequenos mamíferos não voadores ocorrentes no limite sul de distribuição da Mata Atlântica - Machado, Paulo Henrique Damasceno (Universidade do Vale do Rio dos Sinos, 2012)
The variety of abiotic resources and food stands as one hypothesis trying to explain the diversity of fauna associated with tropical forests, which can be influenced by variations in the landscapes’ heterogeneity. The action of those physical aspects on ecological communities is extremely important for small mammals. The ecological aspects of the landscape that is susceptible to variations may explain the differences in geographic distributions presented by small mammals, besides influencing the composition of the communities, mainly due to effects of fragmentation and habitat isolation. This study aimed to investigate the abundance and spatial variation of non-flying small mammals of Parque Estadual de Itapuã (PEI), Viamão, RS (30°20'45,09 "S, 51°01'33, 27" W) evaluating the relationship between landscape heterogeneity, resource availability and abundance in populations of three species of rodents from the Sigmodontinae subfamily (Oligoryzomys nigripes, Akodon montensis and Sooretamys angouya) that showed an extensive geographic distribution in Brazil and susceptibility to influences from the landscape. The total sampling effort was 2,520 traps/night, in which 167 individuals from three species were captured. The most abundant species was A. montensis (N = 117), and the less abundant was S. angouya (N = 19). There was a significant difference regarding species abundance between areas and between seasons (H = 10.874, df = 4, P = 0.028). The availability of resources varied significantly among seasons but not between areas. Aspects of micro-habitat differed among the areas, thus contributing to the formation of clusters in the PCA. So, we consider the composition of the areas studied apparently has the greatest relevance upon aspects related to the potential use and habitat occupation by those three species, and their abundance variations are justified by intrinsic aspects from the vegetation, associated with seasonal climatic changes.
Keywords: Pequenos mamíferos; Parque estadual de Itapuã; Heterogeneidade espacial; Small mammals; Spatial heterogeneity; ACCNPQ::Ciências Biológicas::Biologia Geral